2023
DOI: 10.1161/circresaha.122.321939
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Extracellular Vesicle-Propagated microRNA Signature as a Vascular Calcification Factor in Chronic Kidney Disease

Abstract: BACKGROUND: Chronic kidney disease (CKD) accelerates vascular calcification via phenotypic switching of vascular smooth muscle cells (VSMCs). We investigated the roles of circulating small extracellular vesicles (sEVs) between the kidneys and VSMCs and uncovered relevant sEV-propagated microRNAs (miRNAs) and their biological signaling pathways. METHODS AND RESULTS: We established CKD models in rats and mice by adenine-induced tubulointers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 55 publications
(81 reference statements)
0
15
0
Order By: Relevance
“…[24][25][26][27][28] It was reported that blocking the release of exosomes with GW4869 suppressed several processes of diseases, including atrial fibrillation, kidney disease, chronic airway disease, ulcerative colitis, and ischemia-reperfusion injury. 26,[29][30][31] In our study, we first constructed a BLG-induced CMA mouse model and set the addition of an exosome release inhibitor (GW4869) group. Female mice were used in our study because they exhibited more active Th2 cell activity than male mice.…”
Section: Discussionmentioning
confidence: 99%
“…[24][25][26][27][28] It was reported that blocking the release of exosomes with GW4869 suppressed several processes of diseases, including atrial fibrillation, kidney disease, chronic airway disease, ulcerative colitis, and ischemia-reperfusion injury. 26,[29][30][31] In our study, we first constructed a BLG-induced CMA mouse model and set the addition of an exosome release inhibitor (GW4869) group. Female mice were used in our study because they exhibited more active Th2 cell activity than male mice.…”
Section: Discussionmentioning
confidence: 99%
“…For the induction of pulmonary fibrosis [ 19 ], mice were administered intraperitoneal injections of either 20 mg/kg PQ in 100 μl saline (n = 6) or an equivalent volume of saline as a vehicle control (n = 6). For the purpose of treating PQ-induced pulmonary fibrosis, mice were administered GW4869 (2.5 mg/kg) via intraperitoneal injection twice a week [ 20 ], or received intratracheal injection of miR-217-5p antagomir on day 3 following PQ treatment. The lung tissues were collected on day 21 after PQ treatment for subsequent investigation.…”
Section: Methodsmentioning
confidence: 99%
“…GW4869 is a non-competitive neutral sphingomyelinase inhibitor that prevents ILVs formation capable of blocking exosome production [ 63 66 ]. Several studies have shown that calcification can be significantly ameliorated after the use of GW4869 at the cellular level or in mice models [ 67 69 ], or that GW4869 partially reverses substances that act as inhibitors of calcification [ 70 , 71 ]. These two reviews provide a detailed assessment of the major drugs currently interfering with the biosynthesis or release of EVs [ 65 , 72 ].…”
Section: Overview Of Extracellular Vesiclesmentioning
confidence: 99%
“…Guava FACS analysis of EV from dialysis patients at T0 showed that only endothelium-derived EVs were up-regulated among most circulating EVs derived from monocytes/macrophages, platelets and endothelial cells in CKD patients compared with healthy recipients, indicating that endothelial cells are the main participants in circulating EVs in CKD patients [ 259 ]. A recent study suggests that by transcriptomic analysis of circulating sEVs from CKD mice models as well as from CKD patients, possibly from endothelial cells, the calcification-protecting miRNAs that target VEGFA signaling in CKD-driven vascular calcification are lacking: miR-16-5p, miR-17-5p, miR-20a-5p, and miR-106b-5p [ 67 ]. And the sEVs biogenesis system inhibitor GW4869 [ 63 65 ], was used to ameliorate aortic VC in CKD model mice [ 67 ].…”
Section: The Crosstalk In Vascular Calcificationmentioning
confidence: 99%